2005
DOI: 10.1007/s00262-005-0666-5
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-mediated targeting of human single-chain class I MHC with covalently linked peptides induces efficient killing of tumor cells by tumor or viral-specific cytotoxic T lymphocytes

Abstract: Soluble forms of human MHC class I HLA-A2 were produced in which the peptide binding groove was uniformly occupied by a single tumor or viral-derived peptides attached via a covalent flexible peptide linker to the N terminus of a single-chain beta-2-microglobulin-HLA-A2 heavy chain fusion protein. A tetravalent version of this molecule with various peptides was found to be functional. It could stimulate T cells specifically as well as bind them with high avidity. The covalently linked single chain peptide-HLA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Using an SCT construction scheme very similar to ours, Greten et al (17) showed that the TAX.␤ 2 m.A2 and FluM1.␤ 2 m.A2 constructs could be expressed as Ig fusion proteins and used to stain cells. More recently, another group linked an A2 SCT with a highly immunogenic peptide to an antibody single chain variable domain specific for a tumor-associated antigen (19). Tumor cells expressing this antigen could be coated with the bi-functional recombinant protein and were lysed by CTL specific for the MHC-I SCT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using an SCT construction scheme very similar to ours, Greten et al (17) showed that the TAX.␤ 2 m.A2 and FluM1.␤ 2 m.A2 constructs could be expressed as Ig fusion proteins and used to stain cells. More recently, another group linked an A2 SCT with a highly immunogenic peptide to an antibody single chain variable domain specific for a tumor-associated antigen (19). Tumor cells expressing this antigen could be coated with the bi-functional recombinant protein and were lysed by CTL specific for the MHC-I SCT.…”
Section: Discussionmentioning
confidence: 99%
“…Thus these HLA-I SCTs clearly passed ER quality control, and linkers were accommodated such that the proper folding was detected by mAbs specific for the native, fully assembled HLA-I molecules. It is noteworthy that a construct similar to our G280-9V.␤ 2 m.A2 SCT was expressed as a recombinant protein (19); however, for certain applications such as DNA vaccination (46,47), it was critical to verify cell surface expression in mammalian cells where the SCT faces competition with endogenous ␤ 2 m, peptides, and molecular chaperones.…”
Section: Design and Characterization Of Hla-i Scts-mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, sc Fv Ab fragments were genetically fused to a monomeric scHLA-A2 molecule, which was linked covalently via a flexible linker to the b2m stabilizing subunit, containing a specific peptide in its groove. The same group has also constructed soluble forms of human MHC class I HLA-A2 in which the peptide-binding groove was occupied by a tumor or viral-derived peptide attached via a covalent flexible peptide linker to the N terminus of the single-chain HLA-A2 heavy-chain fusion protein (Oved et al, 2005). The scHLA-A2-peptide complex proved active and capable of staining TCRs after tetramerization.…”
Section: Ab-mhc Conjugatesmentioning
confidence: 99%
“…The peptide cross-linked to MHC was well recognized by specific T cells in vitro and was active in preventing tumor growth in vivo after systemic injection. Alternatively, the peptide can be genetically fused directly to the MHC heavy chain or through the h 2 -microglobulin (44,45). One limitation of the present study is that we showed tumor growth inhibition by early systemic injection of our conjugates but not yet regression of growing tumors.…”
Section: Discussionmentioning
confidence: 47%